Institutional harmonization and its costs and benefits in the context of EU cooperation with its neighbours: An overview - Anna Kolesnichenko (Center for Social and Economic Research (CASE), 2009)
Institutional harmonization is an important part of European integration, and its effects are more far reaching than the effects of trade liberalization. In its policy towards neighbors (the European Neighborhood Policy, ENP), the EU puts a lot of stress on the desirability of institutional harmonization, at least in certain areas. In particular, the free trade agreements that the EU envisages concluding with its Eastern neighbors will involve substantial harmonization of product standards, competition policy and a range of other policies and processes. At the very least, the harmonization will have to focus on the areas that relate to improvement of market access, i.e. removing restrictions to trade, harmonizing product standards and the systems of quality control etc. But in order to implement the new standards and rules, the EU neighbors will have to reform many related areas, so that the harmonization will encompass the whole system of economic governance. Not only will such a revamp help attaining better access to the EU markets, but also (and probably more importantly) it will stimulate modernization of the neighbors economies and bring much needed efficiency gains. In measurement of benefits of harmonization we refer to two methods: one based on the computable general equilibrium (CGE) modeling of welfare effects of better market access, and the other employing a growth model to estimate the wider effects of European institutions on growth. The estimation of costs of harmonization bases on extrapolation of the analogous costs in other countries, in particular CEE. These costs include expenses by a public sector on introduction of harmonization measures, as well as private sector expenses and investments related to their implementation.
Keywords: B41; F15; P33; 330; Institutional harmonization; European integration; European Neighborhood Policy (ENP); market access; non-tariff barriers; Institutionelle Infrastruktur; Institutioneller Wandel; EU-Nachbarstaaten; Europäische Integration; Nichttarifäre Handelshemmnisse; Markteintritt; EU-Staaten; GUS-Staaten